2018
DOI: 10.1111/jpc.14242
|View full text |Cite
|
Sign up to set email alerts
|

Delayed cord clamping in term large‐for‐gestational age infants: A prospective randomised study

Abstract: Aim To compare the post‐natal effects of delayed cord clamping (DCC) and early cord clamping (ECC) in term large‐for‐gestational age (LGA) infants. Methods This prospective randomised study included 51 term LGA infants. The umbilical cords of these infants were clamped at 15 s in group 1 (ECC group (n = 26)) and at 60 s in group 2 (DCC group (n = 25)). Data for Apgar scores, cord blood, pH and lactate values, second haematocrit, 24th bilirubin levels, duration of hospital stay and admission to the neonatal int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 35 publications
0
14
1
Order By: Relevance
“…As a facilitator of adaptation, DCC decreased the rates of NICU admission by 18.1% in IDMs. In contrast to our results, a previous study reported that respiratory distress was not observed in the ECC group; however, three infants in the DCC group were admitted to the NICU due to transient tachypnea, but this difference was not significant, 6 the relatively smaller sample included in their study may explain this discrepancy.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…As a facilitator of adaptation, DCC decreased the rates of NICU admission by 18.1% in IDMs. In contrast to our results, a previous study reported that respiratory distress was not observed in the ECC group; however, three infants in the DCC group were admitted to the NICU due to transient tachypnea, but this difference was not significant, 6 the relatively smaller sample included in their study may explain this discrepancy.…”
Section: Discussioncontrasting
confidence: 99%
“…In contrast to the results of a previous study conducted to detect the effects of DCC on LGA, which reported that there was no statistically significant difference between the DCC and ECC groups in terms of htc levels measured at the second hour of age. 6 The incidence of polycythemia has been demonstrated to be between 10 and 40% in IDM. 20 A previous study evaluating DCC in term newborns indicated that DCC increases htc levels in term infants but does not change polycythemia incidence.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…not generate adequate intrapulmonary pressure but also proves potentially harmful as entire tidal volume will only enter previously aerated regions due to the much lower airway resistance predisposes to lung injury with overexpansion and intermittent collapse of alveoli causing ventilation perfusion (V/Q) mismatch, persistent pulmonary hypertension and bradycardia that further perpetuates hypoxia with delay in onset of breathing [29,30,35,37]. Thus continuous distending airway pressure by sustained oxygen inflation is the key to mitigating hypoxiainduced inhibition of breathing [53,54].…”
Section: Discussionmentioning
confidence: 99%
“…A DCC of ≥ 30 seconds is reportedly associated with higher levels of hematocrit after birth and improved levels of iron during infancy. [19][20][21][22][23][24][25][26][27][28][29][30][31] In preterm newborns who do not require resuscitation, DCC may be effective as it lowers the need for blood pressure management and blood transfusion and improves survival (Class IIa, Level B-R). [32][33][34][35][36][37][38][39] However, there is little evidence supporting early or DCC in term or preterm newborns who require resuscitation at birth (Class IIb, Level C-EO).…”
Section: Umbilical Cord Managementmentioning
confidence: 99%